A darker domain - McDermid, Val , 1955- (HarperCollins, 2009)
1984, Fife.Heiress Catriona Maclennan Grant & her baby son are kidnapped.The ransom payoff goes horribly wrong.She is killed while her son disappears without trace. 2008, Tuscany.A jogger stumbles upon dramatic new evidence that re-opens the cold case.For Detective Sergeant Karen Pirie, it's an opportunity to make her mark.